2013
DOI: 10.1016/j.bpj.2013.07.054
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Mechanically Coupled Myosins Exhibit Group Size-Dependent Regimes

Abstract: Naturally occurring groups of muscle myosin behave differently from individual myosins or small groups commonly assayed in vitro. Here, we investigate the emergence of myosin group behavior with increasing myosin group size. Assuming the number of myosin binding sites (N) is proportional to actin length (L) (N = L/35.5 nm), we resolve in vitro motility of actin propelled by skeletal muscle myosin for L = 0.2-3 μm. Three distinct regimes were found: L < 0.3 μm, sliding arrest; 0.3 μm ≤ L ≤ 1 μm, alternation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 52 publications
4
49
1
Order By: Relevance
“…Outside the cellular context, properties of the main isoforms of myosin II motors (skeletal muscle, smooth muscle, non-muscle A and B) can be studied in motility assays [8][9][10] and actomyosin gels [11][12][13][14][15]. In the latter case, one often works with myosin II minifilaments from skeletal or smooth muscle, because they are easier to prepare and to control than those from non-muscle myosin II.…”
Section: Introductionmentioning
confidence: 99%
“…Outside the cellular context, properties of the main isoforms of myosin II motors (skeletal muscle, smooth muscle, non-muscle A and B) can be studied in motility assays [8][9][10] and actomyosin gels [11][12][13][14][15]. In the latter case, one often works with myosin II minifilaments from skeletal or smooth muscle, because they are easier to prepare and to control than those from non-muscle myosin II.…”
Section: Introductionmentioning
confidence: 99%
“…4 C). Our recent model for skeletal muscle myosin showed that Post myosins are required for a rapid progression of Pre myosins through the main power stroke (8). We hypothesized that, similarly, a stabilization of smooth muscle myosins in the Post state should lead to a more persistent stepping from the Pre to the Post state, and thus more persistent mechanochemical activity.…”
Section: Mechanistic Mathematical Model Of Actin Propulsionmentioning
confidence: 95%
“…We simulated myosin group kinetics by adapting our recently developed mathematical model of the in vitro propulsion of actin filaments (8) to include the effect of P i and ADP on individual smooth muscle myosin kinetics (Fig. 4).…”
Section: Mechanistic Mathematical Model Of Actin Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this measurement scheme would be useful for understanding the cooperativity of multiple motor proteins working in close proximity. While the current study only employed isolated molecules of processive linear motors for demonstration, the developed microscopy is also applicable to other subjects involving linear motor proteins, including cooperative transport of a single cargo by multiple linear motors [43][44][45] and cooperativity among multiple myosin-II heads on a thick filament of muscle [46,47]. Aside from linear motor proteins, measurement of multiple proteins in a rotatory motor system [31,32] and molecular complexes of membrane proteins [20,33] could also be potential applications.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%